Self-Sufficient PV-H₂ Alternative Energy Objects - Kleperis, J.; Solovey, V.V.; Fylenko, V.V.; Vanags, M.; Volkovs, A.; Grinberga, L.; Shevchenko, A.; Zipunnikov, M. (Проблемы машиностроения, 2016)
Energy storage becomes more important as mankind switch to renewable energy, away from fossil resources. Traditional way – batteries - offer a limited number of cycles, require regular maintenance; nevertheless gravitational storage, flywheels, compressed air are mainly large scale and expensive methods. The hydrogen as energy carrier and hydrogen fuel cells are possible option to store different amounts of energy for relatively long times with low losses. Different solutions for self-sufficient sun/wind energy objects are analysed - the solar radiation collecting systems, wind power generators, and high pressure electrolysis technologies for hydrogen production and the metal-hydride energy storage. This article describes the development of a versatile technology that can be used to provide continuous power for small and medium-sized selfsufficient objects or their micro-grids using alternative energy and energy storage. The technology uses advanced electrolysis and fuel cells to efficiently store excess energy from sun/wind generation as hydrogen for later use in fuel cells.